A new root-knot nematode, Meloidogyne vitis sp. nov. (Nematoda: Meloidogynidae), parasitizing grape in Yunnan. - Yanmei Yang; Xianqi Hu; Pei Liu; Li Chen; Huan Peng; Qiaomei Wang; Qi Zhang (PLoS ONE, 2021)
An unknown root-knot nematode was found at high density on grape roots collected from Yunnan Province. Morphometric traits and measurements, isozyme phenotypes, and molecular analysis clearly differentiated this nematode from previously described root-knot nematodes. This new species is described, illustrated and named Meloidogyne vitis sp. nov. The new species can be distinguished from other Meloidogyne spp. by a unique combination of characters. Females display a prominent neck, an excretory pore is located on the ventral region between 23rd and 25th annule behind lips, an EP/ST ratio of approximately 2.5 (1.98-2.96), a perineal pattern with two large and prominent phasmids, and a labial disc fused with the medial lips to form a dumbbell-shaped structure. Males display an obvious head region, a labial disc fused with the medial lips to form a dumbbell-shaped structure, no lateral lips, a prominent slit-like opening between the labial disc and medial lips, a distinct sunken appearance of the middle of the medial lips, and four incisures in the lateral field. Second-stage juveniles are characterized by a head region with slightly wrinkled mark, a labial disc fused with the medial lips to form a dumbbell-shaped structure, a slightly sunken appearance of the middle of the medial lips, a slit-like amphidial openings between the labial disc and lateral lips, and four incisures in the lateral field. The new species has rare Mdh (N3d) and Est phenotypes (VF1). Phylogenetic analysis based on ITS1-5.8S-ITS2, D2D3 fragments of rDNA, and coxI and coxII fragments of mtDNA sequences clearly separated the new species from other root-knot nematodes, and the closest relative was Meloidogyne mali. Meloidogyne mali was collected for amplifying these sequences as mentioned above, which were compared with the corresponding sequences of new species, the result showed that all of these sequences with highly base divergence (48-210 base divergence). Moreover, sequence characterized amplified region (SCAR) primers for rapid identification of this new species were designed.